Recent Advances in Lentiviral Vaccines for HIV-1 Infection - Norton, Thomas D.; Miller, Elizabeth A. (Frontiers in Immunology, 2016)
The development of an effective HIV vaccine to prevent and/or cure HIV remains a global health priority. Given their central role in the initiation of adaptive immune responses, dendritic cell (DC)-based vaccines are being increasingly explored as immunotherapeutic strategies to enhance HIV-specific T cells in infected individuals and thus promote immune responses that may help facilitate a functional cure. The use of HIV-1 based lentiviral vectors as DC-targeting vaccine vectors offers the advantage of transducing non-dividing cells and integrating into the target cell genomic DNA, allowing for expression of encoded antigens over the lifespan of the cell. Moreover, lentiviral vectors may express additional immunostimulatory and immunoregulatory proteins that enhance DC function and direct antigen-specific T cells responses. Recent basic and clinical research efforts have broadened our understanding of lentiviral vectors as DC-based vaccines. In this review, we provide an overview of the pre-clinical and clinical lentiviral vector vaccine studies for treating HIV to date. We also discuss advances in lentiviral vector designs that have enhanced DC transduction efficiency, target cell specificity, immunogenicity, and address potential safety concerns regarding lentiviral vector-based vaccines.